2021
DOI: 10.1002/jsfa.11053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic chromium sources on growth performance, lipid metabolism, antioxidant status, breast amino acid and fatty acid profiles in broilers

Abstract: BACKGROUND Trivalent chromium (Cr) is involved in carbohydrate, lipid, protein and nucleic acid metabolism in animals. This study evaluated the effects of different organic Cr forms with Cr methionine (CrMet), Cr picolinate (CrPic), Cr nicotinate (CrNic), and Cr yeast (Cr‐yeast) at the level of 400 μg kg−1 Cr, on growth performance, lipid metabolism, antioxidant status, breast amino acid and fatty acid profiles of broilers. In total, 540 one‐day‐old Arbor Acres male broilers were randomly assigned to five trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…This is similar to previous studies. Rajalekshmi al [ 35 ] found that the addition of 100, 200, 400, 800, 1600, and 3200 µg Cr/kg Cr-Pro had no significant effect on the feed intake of broilers under conventional feeding conditions; the addition of 400 µg Cr/kg organic chromium (Cr-Met, Cr-yeast, Cr-Nic, Cr-Pic) in the diet had no significant effect on ADG, ADFI and FCR [ 19 ]. In addition, Ebrahimzadeh et al [ 36 ] reported that adding 200, 400 and 800 µg Cr/kg Cr-Met to the diet had no significant effect on the feed intake of broilers under heat stress; their study pointed out that when 500 and 1000 µg Cr/kg Cr-Met were added to the diet, it significantly increased feed intake and body weight gain of broilers under heat stress [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to previous studies. Rajalekshmi al [ 35 ] found that the addition of 100, 200, 400, 800, 1600, and 3200 µg Cr/kg Cr-Pro had no significant effect on the feed intake of broilers under conventional feeding conditions; the addition of 400 µg Cr/kg organic chromium (Cr-Met, Cr-yeast, Cr-Nic, Cr-Pic) in the diet had no significant effect on ADG, ADFI and FCR [ 19 ]. In addition, Ebrahimzadeh et al [ 36 ] reported that adding 200, 400 and 800 µg Cr/kg Cr-Met to the diet had no significant effect on the feed intake of broilers under heat stress; their study pointed out that when 500 and 1000 µg Cr/kg Cr-Met were added to the diet, it significantly increased feed intake and body weight gain of broilers under heat stress [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that organic chromium has lower toxicity and higher bioavailability than inorganic chromium [ 15 , 16 ]. Under conventional conditions, adding organic chromium can promote the growth, fast metabolism and antioxidant capacity of broilers [ 17 , 18 , 19 ]. Under the condition of heat stress, chromium picolinate (Cr-Pic) supplementation can reduce the level of corticosterone and increase the level of serotonin in broilers, indicating that Cr(III) may have the effect of relieving stress in broilers [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors noticed the positive influence of Camelina cakes and oils (Orczewska-Dudek andPietras, 2019, Ciurescu et al, 2018), Camelina seeds (Zając et al, (Untea et al, 2019) on fatty acids profile of animal origin food. Positive influence of chromium on reduction of fat percentage of meat but no significant influence on fatty acids profile, was also noticed by Mir et al, 2017. Han et al, 2021, proved that organic sources of chromium used in broilers diets led to significant increase of omega 3 fatty acids of breast meat.…”
Section: Resultsmentioning
confidence: 75%
“…Sallam et al (2021) observed increased blood total protein with feeding cows on diets supplemented with PF. It is well known that chromium is involved in protein metabolism (Han et al, 2021). The increase in serum total protein and albumin suggests increased amino acid synthesis in the liver.…”
Section: Blood Measurementsmentioning
confidence: 99%
“…Without affecting other nutrient digestibility, chromium supplementation to the control diet increased CP digestibility. Chromium is involved in protein metabolism (Han et al, 2021). It is well documented that feeding high levels of fatty acids negatively affect nutrient digestibility; however, increased digestibilities of DM (by 4.4, 6.9, and 6.1%), OM (by 6.2, 6.0, and 4.2%), CP (10.9, 8.9, and 6.8%), EE (11.7,9.5,and 7.1%),NSC (13.8,14.6,and 10.9%),and NDF (11.2,18.1 and 15.8%) were observed with diets containing CH, PF, or CHPF, respectively.…”
Section: Nutrient Digestibilitymentioning
confidence: 99%